Analysis of the Effect of Government Expenditure, Tax Revenue, and Road Infrastructure on Economic Growth in Lampung Province - Iqbal Dzaky Afkar; Sishadiyati (PT FORMOSA CENDEKIA GLOBAL, 2023)
Economic growth is essential for the prosperity of a country. Adequate infrastructure facilities, including roads, electricity, and water, are essential to encourage economic activity and ensure equitable development and community welfare. This study aims to determine the impact of government spending, tax revenue, and road infrastructure on economic growth in Lampung Province over 11 years using the Ordinary Least Squares (OLS) method and processed with E-Views 12 software. In this study, multiple regression will be used to examine the effect of the independent variable (Government Expenditure, Tax Revenue, and Road Infrastructure) partially on the dependent variable (Economic Growth). The findings revealed that Economic growth was significantly influenced favorably by transportation infrastructure., while Road Infrastructure showed a significant negative influence. This article highlights the importance of developing a strong transportation system to boost economic growth and improve well-being.